Analysis of Bitma Juice (Beetroot and Honey) on Increasing Hemoglobin Levels in Pregnant Women - Retno Palupi Yonni Siwi; Ilmiatun Nadlifah; Yessy Nur Endah Sary; Reni Yuli Astutik (Universitas STRADA Indonesia, 2025)
Background: Anemia in pregnant women is generally caused by unmet iron needs. The impact of anemia in pregnant women includes, BBLR (Low Birth Weight), IUGR (Intrauterine Growth Restriction), premature birth and postnatal death. Purpose: This study aims to determine the effect of giving BitMa juice (beetroot juice and honey) on increasing hemoglobin levels in pregnant women in PMB Caecilia Yunita Rahayu Malang City. Methods: The design of this study used a quasi-experiment with a pre-test and post-test control group design. The sample of this study was 32 pregnant women with a purposive sampling technique, have Hb levels <11 g/dL, are willing to be research respondents and cooperate by consuming BitMa juice during the research process, are willing to undergo Hb examination during the pre-test and post-test. The independent variable of this study was beetroot juice and honey, the dependent variable of this study was an increase in hemoglobin levels. The analysis used the Independent Sample T-Test. Results: The results of the study showed that the average Hb level of respondents before receiving BitMa juice treatment was 10.24 gr/dL. The average Hb level of pregnant women who were given BitMa juice was 12.85 gr/dL. The results of the Independent T-Test statistical test showed p = 0.000 <0.05, which means that there is an effect of BitMa juice (Beetroot and Honey) on increasing hemoglobin levels in pregnant women with a significant increase in hemoglobin levels of 20%. Conclusion: Giving BitMa juice (Beetroot and Honey) is effective in increasing hemoglobin levels in pregnant women, because of the iron, folic acid, and vitamin C content in beetroot and honey. So pregnant women with anemia are advised to consume BitMa juice.